Efecto de la aplicación de la fertilización química complementada con abonos foliares en el rendimiento agronómico de dos variedades de zanahoria (Daucus carota L) - Chamorro Molina, Angel Fernando (2017)
SUMMARY This research was conducted in the community of San Francisco, Montufar Canton province of Carchi; located at the geographic coordinates 10 ° 064'098 "north latitude 10th 063'008" west longitude at an altitude of 2,800 m.s.n.m. two varieties of carrot from INIAP (Nantes y Chantenay) was used, treatments were formed by two varieties of carrot and doses (low, medium, high and without application) fertilizer. the design was randomized complete block factorial arrangement (A x B) in three repetitions, for differences in the means of all variables with the analysis of variance being used Tukey test at 5% significance were submitted. Determine the dose of chemical fertilizer, with compensation of foliar fertilizer is more efficient in agronomic crop yield carrot, assess which treatment efficient results in agronomic crop yield carrot and economically analyze the treatments were the objectives research. Development and implementation of research the following tasks were performed; soil preparation, soil analysis, demarcation of plots, fertilization, planting, weed control, pest and disease control, application of foliar fertilizers and crop, evaluated efficiency and effectiveness of fertilizers, plant height, leaf number, weight and root size, performance of first and second category and economic analysis of treatments. Determining that the variety Nantes achieved greater statistical significance in the variables evaluated and high agronomic performance, low dose showed greater influence on weight and size of root class performance and throughput, also the Nantes treatment with low doses of fertilizer supplemented foliar fertilizers positively flowed into the development and production of the crop, achieving greater economic profitability.